Chemical studies and biological activities of goniothalamus tapisoides - Mohd Alhafiizh, Zailani (Universiti Malaysia Sarawak (UNIMAS), 2008)
Phytochemical and biological activities studies had been performed on Goniothalamus tapisoides. The samples were divided into root, stem, bark and leaf and were extracted using solvent with increasing polarity. The isolation and purification process were performed using thin layer chromatography, column chromatography and preparative thin layer chromatography. Extensive column hromatography and preparative thin layer chromatography resulted in the isolation of one pure compound (63.4 mg). The pure compound has the molecular mass of 200 g/mol which corresponded to molecular formula of C13H12O2 and melting point of 81.3oC – 83.7oC. Based on spectroscopic information, melting point and comparison with literature data, the compound has been identified as goniothalamin. Goniothalamin was found in all part of the plant except the leaf. Brine shrimp toxicity test were performed on each crude extracts and also goniothalamin. The dichloromethane, chloroform and ethyl acetate crude extracts for all part of Goniothalamus tapisoides except leaf showed toxicity to brine shrimp with LC50 values between 10 ppm to 100 ppm. Goniothalamin also showed toxicity towards brine shrimp with LC50 values between 10 ppm to 100 ppm. Termiticidal activity test was also carried out on root and bark crude extracts. The hexane, dichloromethane, chloroform and ethyl acetate crude extract caused mortality to the termites in the concentration of 1.0% - 10.0%.